MODEL PEMBIAYAAN PENDIDIKAN YANG BERKELANJUTAN: KAJIAN KONSEPTUAL DARI PERSPEKTIF EKONOMI PENDIDIKAN - Umam, Khoirul; Ahmad, Masduki; Rochimah, Heni (STKIP Pesisir Selatan, 2025)
The purpose of this article is to review and propose a conceptual model of sustainable education financing in the context of developing countries, integrating the principles of education economics and fiscal sustainability. The background of this research is based on the fact that many education systems face long-term fiscal pressures, dependence on central funds, and weak financing governance. This research was conducted through a conceptual approach based on a comprehensive literature review. The main sources included books on educational economics theory, indexed scientific journals (Scopus, ERIC), and reports from global institutions such as the OECD, UNESCO, and the World Bank. The analysis was conducted through a narrative synthesis of three main dimensions: fiscal, institutional and political sustainability. The study produced a Sustainable Education Financing (SEF) model consisting of four main components: (1) Revenue Mix Strategy to diversify funding sources; (2) Rule-Based Allocation as a results-based allocation mechanism; (3) Stability Fund and Endowment Fund to anticipate fiscal risks; and (4) Digital-based Integrated Monitoring and Evaluation System. This model promotes efficiency, accountability, and multi-actor participation. The main novelty of this article lies in the development of a financing framework that incorporates an interdisciplinary approach and the principle of long-term sustainability.